The association between age at menarche (AAM) and cardiovascular disease (CVD) risk factors in the MASHAD cohort study - Niloofar Shabani; Sara Saffar Soflaei; Khadijeh Bavafa-Valenlia; Nayereh Esmaeilzadeh; Maryam Mohammadi-Bajgriran; Zahra Namazibaygi; Mohsen Moohebati; Gordon A. Ferns; Habibollah Esmaily; Majid Ghayour-Mobarhan (Scientific Reports)
Abstract Age at menarche may be associated with cardiovascular disease risk factors in different ethnic groups. The purpose of this study was to identify the association of cardiovascular disease (CVD) risk factors with age at menarche (AAM) in Mashhad, the second biggest city in Iran. This was a cross- sectional study based on cohort data of 2353 women (35–65 years) from Mashhad, Iran for whom the age at menarche was reported. Baseline demographic, anthropometric data, and biochemical profiles were also collected. The levels of depression and anxiety were evaluated using a validated Persian version of the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Multiple logistic regression models were used to examine the association between age at menarche with CVD risk factors. Anthropometric parameters, short stature, prevalence of diabetes, and CVD risk were significantly higher in women who were younger at menarche (AAM) in comparison to women with an older AAM. Women with a menstruating age of 11 years had a significantly higher weight (P < 0.001), higher BMI (P < 0.001), lower waist circumference (WC) (P = 0.004), higher hip circumference (HC) (P < 0.001) and higher waist-to-thigh ratio (WTR) (P < 0.001) than women with an AAM of ≥ 15 years. University-educated women and employed women were most likely to have menarche at ≥ 15 years (P < 0.001 and P = 0.012 respectively. In girls who menstruated at age ≤ 11 years old, the odds of having a BMI > 28.7 kg/m2, WC > 96 cm, HC > 105 cm and WTR > 61.96 were higher than girls who menstruated at 13 years old. The odds of height > 155 cm was higher in girls with menarche age of ≥ 15 than 13 years and the odds of having depression scores greater than 12 was lower in menarche age group of ≥ 15 years. The girls with menstruation age of 12 years had higher odds of having diabetes mellitus and HC > 105 cm than girls with menstruation age of 13 years. The odds of demi span exceeded 74 cm and height > 155 cm were higher in girls with menarche age of 14 than 13 years. AAM may be a useful factor to identify women at greater risk of CVD to implement appropriate preventive measures.